Simmel and Shakespeare on Lying and Love. (September 2021) - Balmer, Andrew; Durrant, Michael
This article contributes to the development of the sociology of lying by exploring some of the earliest comments on the topic, which are to be found amongst Georg Simmel's writings about secrecy. We outline Simmel's broader approach to interaction, as an experience that is conditioned upon non-knowledge, and work towards the attribution to him of the discovery of an aesthetic of concealment and revelation. This, we argue, can be used as a founding block in the sociology of lying. We then examine what Simmel has to say about lying specifically and find he falls into contradiction as he tries to link lying to other social forms, such as love, and to the shifting patterns of life which he understood to define modernity. To refine his approach, we look back to the period of early modernity during which questions of self-revelation and concealment are being explored in literature and lived uncertainly. Specifically, we take a detailed look at William Shakespeare's Sonnet 138, for it clearly articulates the complex, relational dynamics of lying and love and allows us to read this back into Simmel's account and explain why he falls into confusion. We then conclude by posing a series of questions and taking the position that sociologists should study lying as a relational phenomenon.